Assessing the Drivers of Enterprise Performance in Developing Countries: The Influence of Entrepreneurial Skills, Market Orientation, and Networking - Laksmi, Putu Ayu Sita (JUSTBEST Journal of Sustainable Business and Management, 2024)
This study aims to analyze the influence of entrepreneurial skills, market orientation, sales orientation, and networks on the performance of MSMEs in Gianyar Regency, Bali, using a quantitative approach. The main problem faced by MSMEs in developing countries, including Indonesia, is the low performance of companies influenced by the lack of entrepreneurial skills, limited market orientation, and suboptimal network management. The method used in this study is multiple regression analysis with data obtained from 126 MSME owners through a questionnaire measuring four independent variables and one dependent variable, namely company performance. The results of the study indicate that entrepreneurial skills and market orientation have a significant influence on MSME performance, with coefficient values of 0.45 and 0.32 respectively, indicating that both have a strong positive impact on company performance. In addition, sales orientation also has a significant effect, although with a smaller effect. Networks have a lower effect on company performance. This study provides recommendations for MSME owners to improve their entrepreneurial skills and market orientation in order to improve their company's competitiveness and performance in an increasingly competitive market.